КОНКУРЕНТНЕ ПОЗИЦІОНУВАННЯ СПІЛЬНОГО ПІДПРИЄМНИЦТВА - Петренко В. С. (International Journal of Innovative Technologies in Economy, 2018)
The article is devoted to the competitive positions of joint venture. The planning of the joint venture activity is carried out primarily by a foreign investor who assesses the competitive advantages of different countries and regions according to the main criteria. Competitiveness of an enterprise can be determined on the basis of the stages of competition development. Joint ventures are submerged in the competitive environment of the world economy more than enterprises operating in national markets. However, regional competition should take into account competition. The region as a kind of intermediate level between the world market and a separate enterprise can greatly facilitate or sharply complicate the conduct of foreign economic activity.